2014
DOI: 10.1021/la5035257
|View full text |Cite
|
Sign up to set email alerts
|

Fast Drying and Film Formation of Latex Dispersions Studied with FTIR Spectroscopic Imaging

Abstract: Drying of thin latex films (∼20 μm) at high drying speeds (of the order of seconds) has been studied by fast chemical imaging. ATR-FTIR spectroscopic imaging combined with a fast "kinetic" mode was used to acquire spectral images without coaddition, enabling the amount of water and homogeneity of the drying film to be studied over time. Drying profiles, constructed from analyzing the water content in each image, show two stages of drying, a fast and a slow region. The formulation of latex dispersions affects t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Ekanayake et al 62 confirmed in NMR depth profiling experiments that the particle concentration gradient is steeper when Pe is increased, as was predicted by Routh and Zimmerman. 46 Kimber et al 63 studied latex films dried at elevated temperatures for which the evaporation rate was very high. With the relatively low thickness of their films, on the order of H = 20 m, Pe was approximately 5.…”
Section: Stratification During Drying: Single Type Of Particlementioning
confidence: 99%
“…Ekanayake et al 62 confirmed in NMR depth profiling experiments that the particle concentration gradient is steeper when Pe is increased, as was predicted by Routh and Zimmerman. 46 Kimber et al 63 studied latex films dried at elevated temperatures for which the evaporation rate was very high. With the relatively low thickness of their films, on the order of H = 20 m, Pe was approximately 5.…”
Section: Stratification During Drying: Single Type Of Particlementioning
confidence: 99%
“… Here, it is assumed that a fraction of SDS molecules is still located at the boundaries between deformed particles. Results of film formation studies based on different techniques have indicated that particles of low‐ T g polymers can deform before drying has completed because of their softness . Since the films dried at 92% are turbid, it is expected that they still contain a small amount of water.…”
Section: Resultsmentioning
confidence: 99%
“…For rapid drying of latex dispersion, the accumulation of latex particles at the surface forms a skin layer, which prevents the particles from redistributing or diffusing in time and restricts the evaporation of water. Water evaporation can only occur via passage through capillaries in the film or diffusion through the polymer itself. , Following Adams and co-authors, we separate the skin formation and progress of polymer diffusion into three separate stages that we depict in Figure . In stage I, the rapid evaporation of surface water causes the polymer NPs to migrate to the surface where they are captured when they form part of the skin.…”
Section: Resultsmentioning
confidence: 99%
“…These authors concluded that the drying times of these films of similar thickness, under the same atmospheric conditions, were inversely related to T g . This view is supported by Kazarian et al, who studied the drying of thin latex films by Fourier-transform infrared spectroscopy imaging. They monitored the water content in each image, showing two stages of drying.…”
Section: Introductionmentioning
confidence: 80%